The construction of phosphonate triazolyl by copper()-catalyzed furan dearomatized [3 + 2] cycloaddition - Wahab, Abdul; Gao, Ziwei; Gou, Jing; Yu, Binxun (Organic & biomolecular chemistry, 2022)
Triazole phosphonates are valuable structural motifs in chemical biology and the subject of growing recent interest. A novel methodology to synthesize triazolyl phosphonates starting from furfuryl phosphonate alcohols and organo-azides was developed. This method involved an intermolecular copper-catalyzed dearomatized [3 + 2] cycloaddition/furan ring-opening cascade reaction. A strategy involving a three-component reaction was realized for quick access to triazole phosphonates. Synthesis of triazolyl phosphonates, valuable structural motifs in chemical biology, starting from furfuryl phosphonate alcohols and organo-azides, using an intermolecular copper-catalyzed dearomatized [3 + 2] cycloaddition/furan ring-opening cascade reaction.